Retail Operations. How to run your own store - Lim, Sarah; Tang, Angie (Singapore Pearson Prentice Hall, 2008)
This concise and reader friendly book is for aspiring businessmen and women who desire to be successful. It talks about operational details and the day-to-day running of a shop or chain of stores. The 4-colour book includes pictures of store layouts, merchandise displays and promotional activities so that important points are depicted in a clearer manner. Target Market * Owners of small and medium businesses * Start up entrepreneurs * Retail staff or someone running a retail store or business * Students taking retail modules and courses
Age Group: Adult